1958
DOI: 10.1111/j.1365-2672.1958.tb00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Drying of Steam Sterilized Dressings

Abstract: The degree of vacuum and time of application needed to dry steam sterilized dressings has been investigated. If the steam supply is diy, and the pressure in the drying stage is reduced to an absolute pressure of 50 mm Hg, dressings will be cool and dry without holding the vacuum, provided they are not damp before sterilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1959
1959
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…With the towels used in these experiments it was found that their moisture content averaged about 45 % before sterilization so that a gain in moisture of over 1-5% would mean that the towels would be subjectively damp (Penikett et al, 1958). Experiments with tightly packed drums containing 20 to 25 towels showed that the moisture gain was only slightly higher than that in loosely packed drums but that in the few experiments conducted with packs of eight towels wrapped in two similar towels the percentage moisture gain was much less than with drums.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With the towels used in these experiments it was found that their moisture content averaged about 45 % before sterilization so that a gain in moisture of over 1-5% would mean that the towels would be subjectively damp (Penikett et al, 1958). Experiments with tightly packed drums containing 20 to 25 towels showed that the moisture gain was only slightly higher than that in loosely packed drums but that in the few experiments conducted with packs of eight towels wrapped in two similar towels the percentage moisture gain was much less than with drums.…”
Section: Resultsmentioning
confidence: 99%
“…Hg absolute (Penikett, Rowe, and Robson, 1958). However, these authors state that in their experiments the load achieved a moisture content of less than 5 % and was by their definition 'dry' when the pressure in the chamber was reduced to about 300 mm.…”
Section: The Degree Of After-vacuummentioning
confidence: 91%
See 2 more Smart Citations